A Haptic Interface "Force Blinker 2" for Navigation of the Visually Impaired - Ando, T.; Tsukahara, R.; Seki, M.; Fujie, M. G. (IEEE transactions on industrial electronics (1982), 2012)
In this paper, we develop a new haptic interface called "Force Blinker 2" to navigate the visually impaired. In Force Blinker 2, rotating weights and repulsive magnets are used to reduce the force generated in the opposite direction to the traveling direction, which caused false recognition in the previous system, "Force Blinker 1." In Force Blinker 2 [diameter: 30 (mm), weight: 365 (g)], based on the balance of the centrifugal force of the weight and repulsive force of permanent magnets, the rotational radius of the weight varies depending on the velocity of the rotational weight. First, from a mechanical and control performance perspective, it has been confirmed using an encoder and high-speed camera that the rotational angle, velocity, and weight position are well controlled. Second, ten visually impaired subjects evaluated Force Blinker 2 by comparing it with Force Blinker 1, a fixed radius type interface. The directions presented by Force Blinker 2 were correctly recognized at a rate of approximately 85%, which is about a 10% improvement over the rate achieved by Force Blinker 1. This means the effect of decreasing the force in the opposite direction to the traveling direction on recognition thereof yields about a 10% improvement in recognition performance. In the future, we intend to integrate a route decision system with a cane containing the built-in haptic interface.